Consuming viscous prey: a novel protein-secreting delivery system in neotropical snail-eating snakes - Zaher, Hussam; Oliveira, Leonardo de [UNESP]; Grazziotin, Felipe G.; Campagner, Michelle; Jared, Carlos; Antoniazzi, Marta M.; Prudente, Ana L. (Biomed Central Ltd., 2014)
Background: Efficient venom delivery systems are known to occur only in varanoid lizards and advanced colubroidean snakes among squamate reptiles. Although components of these venomous systems might have been present in a common ancestor, the two lineages independently evolved strikingly different venom gland systems. In snakes, venom is produced exclusively by serous glands in the upper jaw. Within the colubroidean radiation, lower jaw seromucous infralabial glands are known only in two distinct lineages-the basal pareatids and the more advanced Neotropical dipsadines known as goo-eating snakes. Goo-eaters are a highly diversified, ecologically specialized clade that feeds exclusively on invertebrates (e. g., gastropod molluscs and annelids). Their evolutionary success has been attributed to their peculiar feeding strategies, which remain surprisingly poorly understood. More specifically, it has long been thought that the more derived Dipsadini genera Dipsas and Sibynomorphus use glandular toxins secreted by their infralabial glands to extract snails from their shells.Results: Here, we report the presence in the tribe Dipsadini of a novel lower jaw protein-secreting delivery system effected by a gland that is not functionally related to adjacent teeth, but rather opens loosely on the oral epithelium near the tip of the mandible, suggesting that its secretion is not injected into the prey as a form of envenomation but rather helps control the mucus and assists in the ingestion of their highly viscous preys. A similar protein-secreting system is also present in the goo-eating genus Geophis and may share the same adaptive purpose as that hypothesized for Dipsadini. Our phylogenetic hypothesis suggests that the acquisition of a seromucous infralabial gland represents a uniquely derived trait of the goo-eating clade that evolved independently twice within the group as a functionally complex protein-secreting delivery system.Conclusions: The acquisition by snail-eating snakes of such a complex protein-secreting system suggests that the secretion from the hypertrophied infralabial glands of goo-eating snakes may have a fundamental role in mucus control and prey transport rather than envenomation of prey. Evolution of a functional secretory system that combines a solution for mucus control and transport of viscous preys is here thought to underlie the successful radiation of goo-eating snakes.
Keywords: Phylogeny; Evolution; Dipsadinae; Glands; Secretion; Muscles; Goo-eaters